Quantifying Short-Term Foraging Movements in a Marsupial Pest to Improve Targeted Lethal Control and Disease Surveillance - Yockney, Ivor J.; Latham, M. Cecilia; Rouco, Carlos; Cross, Martin L.; Nugent, Graham (PloS one, 2015)
In New Zealand, the introduced marsupial brushtail possum (Trichosurus vulpecula) is a pest species subject to control measures, primarily to limit its ability to transmit bovine tuberculosis (TB) to livestock and for conservation protection. To better define parameters for targeted possum control and TB surveillance, we here applied a novel approach to analyzing GPS data obtained from 44 possums fitted with radio-tracking collars, producing estimates of the animals' short-term nocturnal foraging patterns based on 1-, 3- or 5-nights' contiguous data. Studies were conducted within two semi-arid montane regions of New Zealand's South Island High Country: these regions support low-density possum populations (<2 possums/ha) in which the animals' home ranges are on average larger than in high-density populations in forested habitat. Possum foraging range width (FRW) estimates increased with increasing monitoring periods, from 150-200 m based on a single night's movement data to 300-400 m based on 5 nights' data. The largest average FRW estimates were recorded in winter and spring, and the smallest in summer. The results suggest that traps or poison-bait stations (for lethal control) or monitoring devices (for TB surveillance), set for > 3 consecutive nights at 150 m interval spacings, would likely place >95% of the possums in this type of habitat at risk of encountering these devices, year-round. Modelling control efficacy against operational expenditure, based on these estimations, identified the relative cost-effectiveness of various strategies that could be applied to a typical aerial poisoning operation, to reduce the ongoing TB vectorial risk that possums pose in the High Country regions. These habitat-specific findings are likely to be more relevant than the conventional pest control and monitoring methodologies developed for possums in their more typical forested habitat.